Factors Influencing Sales Manager Effectiveness: Preliminary Findings and Future Research Directions - Lee, Nicholas; Cadogan, John (School of Management Working Papers, 1998)
Ruthlessness is a relatively unexplored concept within the marketing discipline. However, recent evidence has suggested it is linked to organisational and managerial performance. The authors examine the theoretical background and provide a foundation for future research by delineating the construct' s domain. The results of a qualitative study examining the usage of the term "ruthless" in national news and business publications are also reported and discussed. Limitations and directions for future research are then examined.